Assistance in the Implementation of the Pancasila Student Profile Strengthening Project (P5) through the Leaf Painting Method at SDN 01 Balongrejo Elementary School - Zakiyatul Abidah; M. Fathor Rohman; Ahmad Maujuhan Syah; Rahmat Adi Firmansyah; Fitroh Aji (Keris: Journal of Community Engagement, 2026)
The Pancasila Student Profile Strengthening Project (P5) is an innovative program introduced through the Merdeka Curriculum to develop students’ character based on the values of Pancasila. The Pancasila Student Profile comprises six key dimensions: faith and piety, noble character, global diversity, collaboration, independence, creativity, and critical thinking. This community service activity employed the Asset-Based Community Development (ABCD) approach. The asset mapping process identified human resources at SDN 01 Balongrejo as a potential asset requiring further development. To address this need, the leafpaint method, a painting activity using leaves as the primary medium, was implemented. This program aimed to introduce P5 learning through the leafpaint method, provide teachers with innovative instructional practices, enhance students’ creativity and teamwork, and increase awareness of the educational value of local environmental resources. The implementation process consisted of five stages: planning, socialization, execution, mentoring, and evaluation. The participants were fourth- and fifth-grade students of SDN 01 Balongrejo. The results indicate that the activity generated positive outcomes for both students and teachers. Students gained a better understanding of P5 activities, developed creative skills, and learned to utilize natural materials in producing artwork. Teachers acquired an alternative learning innovation that can be integrated into P5 implementation. Overall, the leafpaint method proved effective in supporting P5 activities and contributed positively to the development of students’ creativity, collaboration, and environmental awareness at SDN 01 Balongrejo.